Self‐assembled, fluorine‐rich porous organic polymers: a class of mechanically stiff and hydrophobic materials - Mukherjee, S; Zeng, Z; Shirolkar, M; Samanta, P; Chaudhari, A; Tan, J; Ghosh, S (Wiley, 2018)
Fluorous organic building blocks were utilized to develop two self-assembled, hydrophobic, fluorinated porous organic polymers (FPOPs), namely, FPOP-100 and FPOP-101. Comprehensive mechanical analyses of these functionalised triazine network polymers marked the introduction of mechanical stiffness among all porous organic network materials; the recorded stiffnesses are analogous to those of their organic-inorganic hybrid polymer congeners, that is, metal-organic frameworks. Furthermore, this study introduces a new paradigm for the simultaneous installation of mechanical stiffness and high surface hydrophobicity into polymeric organic networks, with the potential for transfer among all porous solids. Control experiments with non-fluorinated congeners underlined the key role of fluorine, in particular, bis-trifluoromethyl functionalization in realizing the dual features of mechanical stiffness and superhydrophobicity.